2015
DOI: 10.1016/s0924-9338(15)30942-1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Social Withdrawal in Early Adolescence: Epidemiological Data On Italian Hikikomori

Abstract: IntroductionThe Japanese Saito coined the term “hikikomori” to define an extreme form of social withdrawal, particularly present in Japan (1998). In the West there is an increasing frequency of adolescents hikikomori.Objectives and AimsThe UFSMIA Arezzo has received a number of requests to take care of adolescents bearing strong similarities to hikikomori teenagers or “on the way of the social withdrawal”. These admissions have led to an epidemiological study in order to quantify these behaviors among very you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A recent preliminary study has shown blood biomarkers uric acid and high-density lipoprotein cholesterol as possibly correlated with an underlying biological pathology of hikikomori [ 57 ]. Individual psychological factors including interpersonal problems [ 14 ], coping difficulties, conflicting demands, reduced autonomy [ 58 ], low self-esteem [ 34 ], and a predisposed introverted personality [ 31 ] have been shown to play some role in hikikomori propensity. However, the extent to which these underlying vulnerabilities depend on a biological foundation requires further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent preliminary study has shown blood biomarkers uric acid and high-density lipoprotein cholesterol as possibly correlated with an underlying biological pathology of hikikomori [ 57 ]. Individual psychological factors including interpersonal problems [ 14 ], coping difficulties, conflicting demands, reduced autonomy [ 58 ], low self-esteem [ 34 ], and a predisposed introverted personality [ 31 ] have been shown to play some role in hikikomori propensity. However, the extent to which these underlying vulnerabilities depend on a biological foundation requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of somatization, those with early hikikomori may frequently visit pediatricians about undefined complaints, which presents an opportunity for early detection. Although early screening for hikikomori may be difficult, the symptom of "school refusal" seems to be highly indicative [34][35][36]. One must also consider others on the hikikomori spectrum, who may have no problems attending school but communicate very little with people other than the members of their own families (the "hikikomori affinity group").…”
Section: Factors Associated With the Severity Of Hikikomorimentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the International Test Commission's ( 2016 ) guidelines for adapting tests, aiming to accomplish the following tasks: (i) evaluate any linguistic, psychological, and cultural differences in the population of interest; (ii) analyze the legitimacy of hikikomori, the construct under investigation, in the target linguistic and cultural group; and (iii) verify the suitability of the adaptation design and procedure. In particular, those were fulfilled by means of a targeted review of the literature on hikikomori in the Italian context (Crepaldi, 2019 ; Hikikomori Italia, 2017 ; Poletto, 2018 ; Ranieri et al, 2015 ; Sarchione et al, 2015 ), supported by independent psychological and clinical expertise, ultimately suggesting the adaptability of the final version of the scale to the Italian context.…”
Section: Methodsmentioning
confidence: 99%
“…In light of the recent emergence of the phenomenon in several contexts, including European countries (Chauliac et al, 2017 ; Ferrara et al, 2020 ; Malagón‐Amor et al, 2015 ), and Italy, in particular (Crepaldi, 2019 ; Hikikomori Italia, 2017 ; Poletto, 2018 ; Ranieri et al, 2015 ; Sarchione et al, 2015 ), we believe that a psychometric assessment of hikikomori in European contexts and populations will provide researchers, clinicians, mental health practitioners, and policymakers with a useful tool to timely identify those at risk and facilitate the implementation of strategic prevention and intervention in both community and clinical settings.…”
Section: Introductionmentioning
confidence: 99%